Kondisi Tutupan Mangrove Sebelum dan Sesudah Tsunami Tahun 2018 dan Tingkat Keragaman Spesies Mangrove di Pesisir Pantai Mamboro Kota Palu - Fadli, Muhammad; Hamzah, A. Hadian Pratama; Sodikin, Sodikin (SENTRI: Jurnal Riset Ilmiah, 2025)
This research evaluates changes in density and coverage of mangrove vegetation in the Mamboro coastline between 2018 and 2025 using the NDVI index from Sentinel-2 imagery. In 2018, the area of mangroves was recorded at 89.25 hectares, dominated by sparse and moderate density classes, reflecting degradation due to human activities and tsunami impacts. By 2025, the mangrove area increased to 183.07 hectares, but was dominated by moderate and sparse classes, while the dense class actually decreased. This indicates that although the area has increased, the quality of the vegetation has declined. Active rehabilitation after the tsunami, through the planting of over 37,000 mangrove seedlings by the government and local communities, contributed to the recovery of previously open areas. The planted species include Rhizophora mucronata, Avicennia marina, and Sonneratia alba. The diversity index shows moderate diversity, but the dominance of certain species remains high. This ecosystem also serves as an important nursery ground for juvenile fish, supporting the productivity of local fisheries. Research findings emphasize the importance of focusing rehabilitation not only on expanding areas but also on improving the quality of vegetation through community-based approaches, regular monitoring, and management policies.